2023
DOI: 10.1021/acsanm.3c03940
|View full text |Cite
|
Sign up to set email alerts
|

Highly Reflective and Transparent Shell-Index-Matched Colloidal Crystals of Core–Shell Particles for Stacked RGB Films

Tom A.J. Welling,
Keisuke Kurioka,
Hikaru Namigata
et al.

Abstract: Colloidal photonic crystals reflect light of a certain wavelength, according to the distance between the particles. While the reflective properties are good, the transparency is often hampered by multiple incoherent scattering events. This loss of transparency is primarily due to the large size and high scattering cross section of the particles in close-packed opals, especially in the shorter visible wavelength regime. In this work, a one-step vertical deposition method was used to assemble ZnS@SiO 2 core−shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…This suggests that making the core size smaller is more effective in enlarging the cores’ motion range than increasing the electrolyte concentration, at least for the parameter range studied here. Smaller core particles come with the downside of a significantly smaller scattering cross section, as well as the scattering strength of the cores decreases roughly with the square of the volume of the particles (see also Figure S9); however, our recent work has shown that core particle sizes of around 100 nm can still facilitate highly reflective colloidal crystals. , It should be noted that the motion range of cores was measured in the DMSO/water mixture instead of deionized water. Although the zeta potentials of core particles in DMSO/water were different from those in water, the zeta potentials decreased with increasing the electrolyte concentration as in water (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that making the core size smaller is more effective in enlarging the cores’ motion range than increasing the electrolyte concentration, at least for the parameter range studied here. Smaller core particles come with the downside of a significantly smaller scattering cross section, as well as the scattering strength of the cores decreases roughly with the square of the volume of the particles (see also Figure S9); however, our recent work has shown that core particle sizes of around 100 nm can still facilitate highly reflective colloidal crystals. , It should be noted that the motion range of cores was measured in the DMSO/water mixture instead of deionized water. Although the zeta potentials of core particles in DMSO/water were different from those in water, the zeta potentials decreased with increasing the electrolyte concentration as in water (Table S1).…”
Section: Resultsmentioning
confidence: 99%